HUBUNGAN PERILAKU PENCEGAHAN ANEMIA DAN STATUS GIZI DENGAN KEJADIAN ANEMIA PADA MAHASISWI PSKPS FAKULTAS KEDOKTERAN ULM - Ridhani, Muhammad Amar Qistan; Skripsiana, Nika Sterina; Muthmainah, Noor; Juhairina, Juhairina (Homeostasis, 2024)
Abstract: According to the World Health Organization (WHO), anemia is a condition in which hemoglobin is insufficient to carry oxygen needed by the body's peripheral tissues with a cut off point < 12 g/dl in non-pregnant women. Based on data from the South Kalimantan Provincial Health Office in 2019, the prevalence of anemia in Banjarmasin City was 25.7%. The incidence of anemia is influenced by anemia prevention behavior and nutritional status. The purpose of this study was to determine the relationship between anemia prevention behavior and nutritional status with the incidence of anemia in PSKPS female students of the Faculty of Medicine ULM. This study used an analytical observational method with a cross sectional approach. The sample of this study amounted to 76 PSKPS students from the Faculty of Medicine ULM from the class of 2020, 2021, and 2022. The sampling technique was proportional stratified random sampling. The data analysis used was the chi square analysis test. The results showed that anemic students were 31.6% and not anemic were 68.4%. Students who had poor anemia prevention behavior were 36.8% and students who had good anemia prevention behavior were 63.2%. Students with thin nutritional status were 28.9% and students with normal-fat nutritional status were 71.1%. The results of the chi square test analysis showed that there was a relationship between anemia prevention behavior and the incidence of anemia (p = 0.002) and nutritional status with the incidence of anemia (p = 0.006) in female students of PSKPS Faculty of Medicine ULM. Keywords: anemia prevention behavior, nutritional status, anemia incidence. Abstrak: Menurut World Health Organization (WHO), anemia adalah suatu kondisi kurangnya hemoglobin untuk membawa oksigen yang dibutuhkan oleh jaringan tubuh dengan cut off < 12 g/dl pada wanita tidak hamil. Berdasarkan data Dinas Kesehatan Provinsi Kalimantan Selatan tahun 2019, prevalensi anemia di Kota Banjarmasin adalah 25,7%. Anemia dapat dipengaruhi oleh perilaku pencegahan anemia dan status gizi. Tujuan penelitian ini adalah mengetahui hubungan perilaku pencegahan anemia dan status gizi dengan kejadian anemia pada mahasiswi PSKPS Fakultas Kedokteran ULM. Penelitian ini menggunakan metode observasional analitik dengan pendekatan cross sectional. Sampel penelitian ini berjumlah 76 orang mahasiswi PSKPS Fakultas Kedokteran ULM dari angkatan 2020, 2021, dan 2022. Teknik pengambilan sampel penelitian ini menggunakan proportional stratified random sampling dengan uji analisis data menggunakan uji analisis chi square. Hasil penelitian menunjukkan mahasiswi yang mengalami anemia sebanyak 31,6% dan tidak anemia sebanyak 68,4%, yang memiliki perilaku pencegahan anemia kurang sebanyak 36,8% dan yang memiliki perilaku pencegahan anemia baik sebanyak 63,2%, status gizi kurus sebanyak 28,9% dan status gizi normal-gemuk sebanyak 71,1%. Hasil analisis uji chi square menunjukkan terdapat hubungan perilaku pencegahan anemia dengan kejadian anemia (p = 0,002) dan status gizi dengan kejadian anemia (p = 0,006) pada mahasiswi PSKPS Fakultas Kedokteran ULM. Kata-kata kunci: perilaku pencegahan anemia, status gizi, kejadian anemia.